Plus-origin mapping of single-stranded DNA plasmid pE194 and nick site homologies with other plasmids. - Sozhamannan, S (1990)
Staphylococcus aureus plasmid pE194 manifests a natural thermosensitivity for replication and can be established in several species, both gram positive and gram negative, thus making it attractive for use as a delivery vector. Like most characterized plasmids of gram-positive bacteria, pE194 generates single-stranded DNA. The direction of pE194 replication is clockwise, as determined by the strandedness of free single-stranded DNA. Significant homology exists between a 50-base-pair sequence in the origin of pE194 and sequences present in plasmids pMV158 (Streptococcus agalactiae), pADB201 (Mycoplasma mycoides), and pSH71 (Lactococcus lactis). We used an initiation-termination reaction, in which pE194 initiates replication at its own origin and is induced to terminate at the related pMV158 sequence, to demonstrate that pE194 replicates by a rolling-circle mechanism; the initiation nick site was localized to an 8-base-pair sequence.